DETEKSI DAN PENYULUHAN PENYAKIT AKIBAT KERJA PADA PENGUPAS KERANG HIJAU DI CILINCING, JAKARTA UTARA - Amalia, Husnun; Hairunisa, Nany; Mashabi, Yasmine; Zaina, Nashita Amira (Universitas Trisakti, 2024)
DKI Jakarta is the most populous city in Indonesia and 59.29% of North Jakarta's population are fishermen, and Cilincing is the largest producer of green mussels in DKI Jakarta with 286 green mussel fishermen (2010), which is 70% of the total number of green mussel fishermen of DKI Jakarta and involves around 1,200 workers. The professions of the community are fishermen and clam collectors (25%), shellfish peel workers (8%), and shellfish traders (6%). The profession of shelling shells is carried out less ergonomically for 6-8 hours a day. This can lead to occupational diseases including Low Back Pain, Frozen shoulder, trigger finger, and the threat of chemical hazards. This service activity aims to detect occupational diseases in green mussel peeling workers and provide preventive information so that the disease does not occur. The consultation and examination activities were attended by 87 residents, aged from 5-84 years. Occupational diseases are mainly found in residents who are still actively working in the Green mussel peeling industry. Occupational diseases are found to be fit for duty in this industry. The lifting officer seemed to lift less ergonomic activities so that abnormalities of Hernia Nucleus Purposus (HNP), myalgia Shoulder pain, and Low Back Pain (LBP) were detected. Scallop peelers complain of low back pain (LBP), neck pain, and Carpal Tunnel Syndrome (CTS). Counseling participants are women working as green mussel peelers aged 20-73. The duration of working hours per day > 5 hours (92.3%). Education level is low (76.9%) and length of work experience varies between 1->30 years. Counseling showed good results, judging from the post-test scores 100% of participants showed good results. Workers need follow-up from various parties to prevent occupational diseases in green mussel peeling workers.